KEMAMPUAN PEMBENTUKAN GEL SURIMI MANYUNG (Arius spp.) PADA BERBAGAI KONDISI PEMANASAN DAN PENCUCIAN - Iwan Y.B. Lelana; Amir Husni (Jurnal Perikanan Universitas Gadjah Mada, 2002)
Manyung is one of low value fish in Yogyakarta. In order to increase the value, manyung was processed into surimi. In this research, manyung was processed into surimi with different heating temperatures (40, 45, 50, 55, 60, and 70oC) and washing time frequency (0, 1, 2, 3, 4, and 5 times) to investigate the gel properties of manyung surimi. Gel strength of manyung surimi increased as washing time treatment increased from 0 to 5 times. Statistical analysis showed that the 4 washing time and 5 washing time have similar gel strength and sensory characteristics. Manyung surimi with 5 washing time and pre-incubation at 60oC followed by cooking at 90oC produced the highest gel strength.